2008
DOI: 10.1021/cg800174n
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Development of an Alternative Approach to Macromolecular Crystallization

Abstract: We are developing an alternate strategy for the crystallization of macromolecules that does not, like current methods, depend on the optimization of traditional variables such as pH and precipitant concentration, but is based on the hypothesis that many conventional small molecules might establish stabilizing, intermolecular, noncovalent cross-links in crystals, and thereby promote lattice formation. Earlier experiments provided encouraging results that suggested further research was warranted (Larson,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…As in previous investigations (Larson et al, 2007(Larson et al, , 2008 smallmolecule components of the crystallization 'cocktails' were found as integral components of the crystals and again were involved in macromolecular interfaces in the lattice. Thus, they provided additional lattice contacts and possibly stabilizing interactions.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As in previous investigations (Larson et al, 2007(Larson et al, , 2008 smallmolecule components of the crystallization 'cocktails' were found as integral components of the crystals and again were involved in macromolecular interfaces in the lattice. Thus, they provided additional lattice contacts and possibly stabilizing interactions.…”
Section: Discussionsupporting
confidence: 67%
“…The crystal screening experiments that yielded the complex crystals have been described in detail elsewhere (Larson et al, 2008). The crystals were grown by vapor diffusion at room temperature in 96-well Intelli-Plates (Hampton Research, Aliso Viejo, California, USA) with 90 ml reservoirs of 25% PEG 3350 in water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous cases have, however, been reported in which small, and sometimes large, molecules were observed to make crucial interactions between macromolecules in the crystal that either helped to guide or secure formation of the lattice (Larson et al, 2008;McPherson & Cudney, 2006). Such small molecules sometimes had a physiological basis for their unexpected presence, but frequently did not.…”
Section: Factors Affecting Crystallization and The Inclusion Of Additmentioning
confidence: 99%
“…Small molecules have been recognized as often being crucial for protein crystallization, but they have seldom been identified within the crystal structure. 67,68 There are also experimental results showing that long alkyl chain imidazolium-based IL ([C 14 MIM]Br) in fact binds to the surface of a globular protein bovine serum aluminum (BSA). 69 In agreement with the mechanisms of IL-protein interactions discussed in our work, it has been found that, at lower concentration, [C 14 MIM]Br binds to the BSA surface due to electrostatic attraction while at higher IL concentration the mechanism is that of hydrophobic interaction.…”
Section: Ils In the Task Of Crystallization: Reaction Environment Vsmentioning
confidence: 99%